LEAN-LED HOSPITAL DESIGN OF COVID MODULAR HOSPITAL IN TANJUNG DUREN, WEST JAKARTA - Shiddiqi Ariadji, Aslam
The Covid-19 (Coronavirus Disease-19) pandemic that has occurred throughout the world has had a tremendous impact on various fronts. PT Pertamina (Persero) through its subsidiary, PT Patra Jasa, built a covid hospital in Tanjung Duren, West Jakarta. This hospital was built at a critical time, where the number of covid patients increased significantly due to the Delta variant, but was completed when the number of covid patients decreased significantly as well. This hospital was built using a modular structural system, so that it can be built and changed according to its use. Due to its specificity for Covid-19 patients, this hospital is designed in a limited manner. This can be seen from the layout of the building, the functions of the room, the relationship from one room to another, and the area of the room in it. The next question is whether the existing design of the building is able to accommodate patients other than Covid-19 patients after the pandemic ends. Lean-led design is a way of designing hospitals based on the experiences of patients, visitors, and health workers. The way of thinking is to require healthcare organizations to evaluate workflows and processes, identify opportunities to eliminate valueless waste, and drive final results before major capital outlays. When exploring new ideas, Lean principles direct the entire project team to keep patients at the forefront of the process and never forget what is best for them. In achieving Lean-Lead design, analysis using the Craft Tool software on the layout and zoning between rooms and buildings is an important consideration. This analysis produces the best proposed model based on software calculations by presenting the cost of each proposal. A good layout needs to be based on the function and area of the room or building in accordance with regulations. Propose major changes in the area of the room and the addition of rooms using the technical guidelines of a class C hospital for the needs of this hospital function.